Vascular loop of the antero-inferior cerebellar artery as a cause of vertigo. Case presentation - Masleidy Valladares Valle; Lariagna Moya Cardoso; Rubén Daniel Fernández Azpiri (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Vascular compression of the vestibule-cochlear nerve can manifest itself with a variety of symptoms, including vertigo, the cause of which is infrequent by vascular loops. We present the case of a 41-year-old male patient who came to the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos for hearing loss and tinnitus in the left ear, as well as dizziness. A simple MRI was performed that showed a vascular loop in the anterior inferior cerebellar artery that entered the internal auditory canal, which explained the symptoms. The patient had clinical improvement after symptomatic treatment. Due to the unusual nature of the entity, the presentation of the case was decided.